High-strength artificial bone repair material and preparation method thereof
By compressing dehydration and freezing and drying during the cross -linking process of collagen and calcium phosphate, the problem of insufficient intensity of collagen sponge mechanics was solved, significantly increased the pressure resistance and density, extended the degradation time of the material, and matched the new new time. Bone growth rate.
Patent Information
- Application Number
- CN202411597662.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-28
AI Technical Summary
The existing collagen sponges have low mechanical strength and are not compressively strong enough to match the strength of cancellous bones. At the same time, compression and densification will lead to a decrease in blood infiltration and hinder the transport of cells and nutrients.
By mixing collagen with calcium phosphate, and compressing dehydration and frozen drying during the cross -linking process, the cross -linking state of collagen hydrogel is adjusted, and the density and compressive strength of the material are improved.
It significantly improves the pressure resistance of artificial bone repair materials, increases the mechanical strength by 10 to 50 times, and at the same time extend the degradation time of the material in the body, matching the growth rate of new bone growth.
Smart Images

Figure CN119367619A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-strength artificial bone repair material and a preparation method thereof, in particular to a high-strength collagen artificial bone repair material and a preparation method thereof. Background Art
[0002] As a raw material for bone repair, tricalcium phosphate materials have excellent degradation properties and can form chemical bonds with bones after implantation in the body, but they still lack sufficient biological activity and cannot further promote the formation of new bones. Some researchers have improved the biological activity of calcium phosphate materials by compounding collagen molecules. Collagen is an important component of human bones and has excellent osteoinductivity, which can induce osteocyte proliferation and differentiation (see the literature: Jiang QS, Wang LRand et al. Canine ACL reconstruction with an injectable hydroxyapatite / collagen paste for accelerated healing of tendon-bone interface. Bioact. Mater. 2023, 20: 1-15).
[0003] However, the mechanical strength of collagen sponge is low, and the compressive strength is generally not higher than 10kPa (referring to literature: Yunoki S., Ikoma T.and et al. Development of collagen condensation method to improve mechanical strength of tissue engineering scaffolds. Mater. Charact. 2010, 61: 907-911.). The strength of cancellous bone is about 2-5MPa, and the strength of collagen sponge is quite different from it. Although, by compounding with materials such as hydroxyapatite, and by compression process molding, the compressive strength of collagen sponge can be significantly improved, but compression densification can cause collagen products to decrease in blood infiltration, hindering the crawling and transportation of cells and nutrients. Therefore, it is urgent to develop a collagen sponge porous bone repair material with a compressive strength close to cancellous bone. Summary of the invention
[0004] The purpose of the present invention is to provide a high-strength artificial bone repair material and a preparation method thereof, which significantly enhances the mechanical strength of the artificial bone repair material while ensuring excellent degradation performance and biological activity.
[0005] The present invention adopts the following technical solution:
[0006] A method for preparing an artificial bone repair material, using collagen and calcium phosphate as raw materials, and forming the artificial bone repair material through the following step S100 or step S200;
[0007] Step S100 includes: mixing a collagen solution and calcium phosphate, and adding a cross-linking agent to obtain a collagen hydrogel, compressing to remove free water in the hydrogel to reduce the volume of the hydrogel, and freeze-drying to form a collagen hydrogel;
[0008] Step S200 includes: preparing calcium phosphate collagen composite particles by mixing collagen and calcium phosphate uniformly, weighing the collagen composite particles and calcium phosphate powder and adding them into a collagen solution, adding a cross-linking agent for cross-linking, and freeze-drying to form.
[0009] In a preferred embodiment, freeze-drying molding includes primary freeze-drying molding and secondary freeze-drying molding. The composite material after the primary freeze-drying molding is immersed in a cross-linking agent solution for secondary chemical cross-linking. The composite material after the secondary chemical cross-linking is cleaned and then subjected to secondary freeze-drying molding to obtain the high-strength artificial bone repair material.
[0010] In a more preferred embodiment, the secondary chemical cross-linking time is 6 to 48 hours, and the cleaning is performed by placing it in pure water and stirring it at 200 to 600 rpm for 6 to 24 hours. The cross-linking agent in the cross-linking agent solution includes a combination of one or more selected from genipin, glutaraldehyde and carbodiimide, and the concentration of the cross-linking agent in the cross-linking agent solution is 0.05 to 5 wt%.
[0011] In a preferred embodiment, in step S100, after adding a cross-linking agent, the mixture is frozen and cross-linked at -40 to -20°C for 0.5 to 7 days, and then restored to room temperature to obtain a collagen white hydrogel; the collagen hydrogel is placed in a compression mold for compression and dehydration, wherein the volume of the collagen hydrogel is compressed to 10 to 70% of the initial volume.
[0012] In a specific and preferred embodiment, step S100 specifically includes:
[0013] Step S101, weighing collagen and adding it to an acid solution to obtain a collagen acid solution, adding calcium phosphate powder and mixing evenly, adding a cross-linking agent and stirring evenly to obtain a slurry, injecting the slurry into a molding mold, freezing cross-linking, demolding and returning to room temperature to obtain a collagen hydrogel;
[0014] Step S102, placing the collagen hydrogel into a compression mold for compression dehydration, and then freeze-drying to obtain a preliminarily formed composite material;
[0015] Step S103, immersing the initially formed composite material in a crosslinking agent solution to perform a second chemical crosslinking, washing the composite material after the second chemical crosslinking with pure water, and performing a second freeze-drying to obtain the high-strength artificial bone repair material.
[0016] In a more preferred embodiment, in step S101, the weight ratio of collagen to calcium phosphate powder is 0.05-1, the mass percentage of collagen in the collagen acid solution is 5-10%, the concentration of the acid solution is 0.2-10wt%, and the concentration of the cross-linking agent in the slurry is 10-500ppm.
[0017] In a preferred embodiment, in step S200, calcium phosphate powder is added to the acid solution of collagen, mixed evenly, freeze-dried and mechanically crushed to obtain calcium phosphate collagen composite particles; the mesh size of the composite particles is 20-300.
[0018] In a more preferred embodiment, in step S200, the collagen composite particles and calcium phosphate powder are added to the collagen acid solution, mixed evenly, and then a cross-linking agent is added and mixed evenly to obtain a slurry, which is then freeze-dried.
[0019] In another specific and preferred embodiment, step S200 specifically includes:
[0020] Step S201, weighing collagen and adding it to an acid solution to obtain a collagen acid solution, adding calcium phosphate powder and mixing evenly, injecting the slurry into a molding mold and freeze-drying to obtain a calcium phosphate collagen composite sponge, and obtaining calcium phosphate collagen composite particles by mechanical crushing;
[0021] Step S202, weighing calcium phosphate collagen composite particles and adding them into an acid solution to obtain acidified calcium phosphate collagen;
[0022] Step S203, weighing collagen and adding it to an acid solution to obtain a collagen acid solution, adding calcium phosphate powder and the calcium phosphate collagen acidified in step S202, mixing evenly, adding a cross-linking agent and stirring evenly, injecting the slurry into a molding mold, and freeze-drying to obtain a preliminarily formed composite material;
[0023] Step S204, immersing the initially formed composite material in a crosslinking agent solution to perform a second chemical crosslinking, washing the composite material after the second chemical crosslinking with pure water, and performing a second freeze-drying to obtain the high-strength artificial bone repair material.
[0024] In a more preferred embodiment, in steps S201 and S203, the weight ratio of collagen to calcium phosphate powder is 0.05-1, the mass percentage of collagen in the collagen acid solution is 5-10%, and the concentration of the acid solution is 0.2-10wt%; in step S202, the concentration of the acid solution is 0.2-10wt%, and the mass ratio of the calcium phosphate collagen composite particles to the acid solution is 0.5-3; in step S203, the mass ratio of collagen to acidified calcium phosphate collagen is 0.03-0.2, and the concentration of the chemical cross-linking agent in the slurry is 10-500ppm.
[0025] In a preferred embodiment, the collagen includes a combination of one or more selected from type I collagen, type II collagen and recombinant collagen, with a weight average molecular weight of 50,000-300,000 Da; the acid solution includes a hydrochloric acid solution or an acetic acid solution, the calcium phosphate includes a combination of one or more selected from tricalcium phosphate, magnesium-containing tricalcium phosphate, hydroxyapatite and octacalcium phosphate, and the cross-linking agent includes genipin and / or glutaraldehyde.
[0026] The principle of improving the mechanical strength of artificial bone repair materials in the present invention is as follows: by regulating the cross-linking state of collagen hydrogel, free water is slowly compressed to remove the densification of the product; the inventor team found that some free water will appear in the collagen hydrogel at a specific stage of the cross-linking process, which can be dehydrated and the product density can be increased by compression, and the remaining bound water will be redistributed during the compression process to help fix the compressed shape during the freeze-drying process; or the collagen and calcium phosphate composite material can be mechanically crushed to obtain composite particles, which are added to a mixed solution of collagen and calcium phosphate after surface acid treatment and activation. Under the action of the cross-linking agent, the surface of the solid composite particles dissolves and complexes with the protein molecules in the solution to form a high-density collagen / tricalcium phosphate composite product.
[0027] The present invention also adopts the following technical solution:
[0028] An artificial bone repair material is prepared according to the above preparation method.
[0029] In a preferred embodiment, the porosity of the artificial bone repair material is 20-80%, and the compressive strength is 0.5-2 MPa.
[0030] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0031] The artificial bone repair material prepared by the present invention has significantly improved density and 10 to 50 times improved compressive strength; after being implanted into the human body, the degradation time can be effectively prolonged, and can better match the growth rate of new bones. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solution of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0033] Figure 1 This is a photo of the artificial bone repair material prepared in Example 1.
[0034] Figure 2 This is a microscopic morphology of the artificial bone repair material prepared in Example 1.
[0035] Figure 3 This is a bar graph showing the compressive strength of the artificial bone repair materials prepared in Example 1 and Comparative Example 1.
[0036] Figure 4 These are photos of the anti-enzymatic degradation experiment of the artificial bone repair materials prepared in Example 1 and Example 3 (30 days, 37° C.). DETAILED DESCRIPTION
[0037] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0038] The components of traditional bone repair materials are mainly a composite of collagen and hydroxyapatite powder, in which the hydroxyapatite content is about 55%. The process is to mix collagen powder and hydroxyapatite and then hot-press them at 90-130 degrees. The product has obvious deficiencies in degradation performance (hydroxyapatite is difficult to degrade in the body) and pore structure (hot-pressed molding is relatively dense).
[0039] Traditional bone repair material preparation technologies also include collagen / hydroxyapatite composite freeze-drying molding method and porous tricalcium phosphate ceramic surface perfusion collagen freeze-drying technology. Among them, the nano-scale hydroxyapatite powder used in the collagen / hydroxyapatite composite freeze-drying molding method has a content of 20-80%, which cannot achieve a higher ceramic phase content, and hydroxyapatite is difficult to degrade in the body. The main body of the porous tricalcium phosphate ceramic surface perfusion collagen freeze-drying technology is sintered calcium phosphate ceramics, which has insufficient matrix toughness and cannot achieve the unique shaping technology of collagen sponge.
[0040] The applicant has previously proposed an improved artificial bone repair material, which uses tricalcium phosphate powder as raw material, and a magnesium-containing tricalcium phosphate material with higher biological activity and full in vivo degradation is compounded with collagen molecules to form a new generation of highly biologically active and degradable artificial bone repair materials. However, in the scheme, the solubility concentration of bovine type I collagen in acid solution is difficult to exceed 10 mg / mL, which seriously restricts the density and mechanical strength of the collagen / tricalcium phosphate composite material.
[0041] The solubility concentration of bovine type I collagen in acid solution is difficult to exceed 10 mg / mL, which seriously restricts the amount of collagen / tricalcium phosphate composite material added after freeze drying. The degradation time of collagen molecules in the body is generally short. The degradation time of bovine type I collagen with a higher molecular weight (about 300kDa) is also difficult to exceed three months, while the regeneration and repair time of bone defects generally requires more than 6 months. Increasing the density of collagen sponge can effectively prolong the degradation time of collagen sponge, but the solubility of collagen material is limited.
[0042] In response to the above problems and phenomena, the inventors innovatively discovered a metastable state of collagen in the chemical cross-linking process. In this state, free water inside the collagen can be removed by extrusion, and the remaining bound water can be distributed in the collagen sponge to reshape the cross-linking network of the collagen sponge, thereby achieving the purpose of compression and densification of the sponge network structure. The pre-prepared surface-acidified calcium phosphate collagen composite particles and calcium phosphate can also be added to the collagen solution, which greatly improves the density of the artificial bone repair material, significantly enhances the compressive strength of the material, and prolongs the degradation time of the bone repair material in the body.
[0043] Furthermore, compared with the traditional collagen compression molding method, the high-strength collagen artificial bone repair material formed by two-step molding has a high degree of cross-linking and its in vivo stability is greatly enhanced.
[0044] The first preparation method of the artificial bone repair material of this embodiment is: mixing the collagen solution with calcium phosphate, adding a chemical cross-linking agent for freeze cross-linking, and obtaining a collagen hydrogel after returning to room temperature, slowly compressing to remove free water and reduce the volume of the hydrogel, and finally forming it by freeze drying.
[0045] The first preparation method specifically comprises the following steps:
[0046] (1-1) Weigh collagen and add it to an acid solution to obtain a collagen acid solution, add calcium phosphate powder and mix well. Then add a cross-linking agent and stir well. Inject the slurry into a molding mold and shake it slightly until the liquid surface is flat. Put the mold into a freezer to freeze and cross-link, then demold and return to room temperature to obtain a collagen hydrogel.
[0047] (1-2) The frozen cross-linked collagen hydrogel is placed in a compression mold for compression dehydration, and then freeze-dried to obtain a preliminarily formed high-strength collagen sponge.
[0048] (1-3) The initially formed high-strength collagen sponge is immersed in a crosslinking agent solution to perform a second chemical crosslinking, and the crosslinked composite material is placed in pure water for stirring and washing, and then freeze-dried to obtain a high-strength collagen artificial bone repair material.
[0049] The process of step (1-1) is specifically as follows: use an analytical balance to weigh collagen and acid solution, add collagen to the acid solution, and use a PTFE stirring paddle at 200-600rpm to stir for 10-30 minutes until completely dissolved. Use an analytical balance to weigh calcium phosphate powder, add all the calcium phosphate powder to the collagen acid solution, and continue stirring for 5-20 minutes until mixed evenly to obtain a mixed slurry. Then, add a cross-linking agent to the mixed slurry and stir for 1-5 minutes. Inject the mixed slurry into a mold, and oscillate the mold to make the slurry liquid level flat. Low-temperature cross-linking for 0.5-7 days in a -40--20°C freezer, demold and return to room temperature to obtain a collagen hydrogel.
[0050] The collagen used in step (1-1) includes but is not limited to type I collagen, type II collagen and recombinant collagen, etc., with a weight average molecular weight of 50000-300000Da. The acid solution includes but is not limited to hydrochloric acid solution, acetic acid solution, etc. The calcium phosphate powder used includes but is not limited to tricalcium phosphate, magnesium-containing tricalcium phosphate, hydroxyapatite and octacalcium phosphate, etc. The cross-linking agent includes but is not limited to genipin, glutaraldehyde, etc. Among them, the mass ratio of the weighed collagen to the calcium phosphate powder is 0.05-1, the mass percentage of collagen in the collagen acid solution is 5-10%, the acid concentration in the acid solution is 0.2-10wt%, and the concentration of the cross-linking agent in the mixed slurry is 10-500ppm.
[0051] The process of step (1-2) is specifically as follows: placing the collagen hydrogel obtained by freeze cross-linking into a compression mold for compression dehydration, and then freeze drying to obtain a preliminarily formed high-strength collagen sponge. The volume of the collagen hydrogel is compressed to 10-70% of the initial volume; preferably 15-50% of the initial volume, and further 20-35% of the initial volume.
[0052] The process of step (1-3) is specifically as follows: immerse the high-strength collagen sponge in a crosslinking agent solution and perform a second chemical crosslinking for 6 to 48 hours. Put the crosslinked collagen sponge into pure water at 200 to 600 rpm for stirring and washing for 6 to 24 hours, and then freeze-dry to obtain a high-strength collagen artificial bone repair material. The crosslinking agent includes but is not limited to genipin, glutaraldehyde, carbodiimide, etc., with a concentration of 0.05 to 5wt%.
[0053] In this preparation method, the discovery that collagen sponge exists in a metastable state during the chemical cross-linking process is utilized. In this state, the free water inside the collagen can be removed by squeezing, and the remaining bound water can be distributed in the sponge to reshape the cross-linked network of the collagen sponge, thereby achieving the purpose of compressing and densifying the sponge network structure. In addition, the high-strength collagen artificial bone repair material formed twice has a high degree of cross-linking and greatly enhanced in vivo stability. Compared with the conventional preparation method, the density of the collagen sponge obtained is significantly improved, and the compressive strength is increased by 10 to 50 times; after implantation into the human body, the degradation time can be effectively extended, which can better match the growth rate of new bone.
[0054] The second preparation method of the artificial bone repair material of this embodiment is: mixing the collagen solution with calcium phosphate and freeze-drying, obtaining calcium phosphate collagen composite particles by mechanical crushing, acidifying the calcium phosphate collagen composite particles, adding them to the mixed solution of collagen and calcium phosphate, adding a cross-linking agent for low-temperature cross-linking, and finally forming them by freeze-drying.
[0055] The second preparation method specifically comprises the following steps:
[0056] (2-1) Weigh collagen and add it to an acid solution to obtain a collagen acid solution, add calcium phosphate powder and mix evenly, inject the slurry into a molding mold, freeze-dry and obtain a calcium phosphate collagen composite sponge, and obtain a calcium phosphate collagen composite powder by mechanical crushing.
[0057] (2-2) weighing calcium phosphate collagen composite particles and adding them into an acid solution to obtain acidified calcium phosphate collagen;
[0058] (2-3) Weigh collagen and add it to the acid solution to obtain a collagen acid solution, then add the acidified calcium phosphate collagen and calcium phosphate powder in sequence, mix well, add a cross-linking agent and stir well. Inject the slurry into a molding mold and shake it slightly until the liquid surface is flat. After freeze drying, a preliminarily formed high-strength collagen artificial bone repair material is obtained.
[0059] (2-4) The initially formed high-strength collagen artificial bone repair material is immersed in a crosslinking agent solution to perform a second chemical crosslinking, and the crosslinked composite material is placed in pure water for stirring and washing, and then freeze-dried to obtain a high-strength collagen artificial bone repair material.
[0060] The process of step (2-1) is specifically as follows: use an analytical balance to weigh collagen and acid solution, add collagen sponge to the acid solution, and use a PTFE stirring paddle at 200-600rpm to stir for 10-30 minutes until completely dissolved. Use an analytical balance to weigh calcium phosphate powder, add all the calcium phosphate powder to the collagen acid solution, and continue stirring for 5-20 minutes until mixed evenly. Then, freeze in a -20 to -40°C refrigerator for 2 to 6 hours and freeze-dry to obtain a calcium phosphate collagen composite sponge. Use a pelletizer to crush the calcium phosphate collagen composite sponge and obtain composite material particles between 20 and 300 meshes.
[0061] The collagen used in step (2-1) includes but is not limited to type I collagen, type II collagen and recombinant collagen, etc., with a weight average molecular weight of 50000-300000Da. The acid solution includes but is not limited to hydrochloric acid solution, acetic acid solution, etc. The calcium phosphate powder used includes but is not limited to tricalcium phosphate, magnesium-containing tricalcium phosphate, hydroxyapatite and octacalcium phosphate, etc. Among them, the mass ratio of collagen to calcium phosphate powder is 0.05-1, the mass percentage of collagen in the collagen acid solution is 5-10%, and the acid concentration in the acid solution is 0.2-10wt%.
[0062] In step (2-2), calcium phosphate collagen composite particles are weighed using an analytical balance and an acid solution is added to acidify the calcium phosphate collagen composite powder to increase the cross-linking activity of collagen molecules on the surface of the calcium phosphate collagen composite powder. The acid solution includes but is not limited to a hydrochloric acid solution and an acetic acid solution, the concentration of the acid solution is 0.2 to 10 wt%, and the mass ratio of the calcium phosphate collagen composite particles to the acid solution is 0.5 to 3.
[0063] The process of step (2-3) is specifically as follows: use an analytical balance to weigh collagen and acid solution, add collagen to the acid solution, and use a PTFE stirring paddle at 200-600rpm to stir for 10-30 minutes until completely dissolved. Then, weigh the above-mentioned calcium phosphate collagen composite particles and calcium phosphate powder and add them to the collagen acid solution, and continue stirring for 5-20 minutes until the mixture is evenly mixed. Then, add a cross-linking agent to the mixed slurry and stir for 1-5 minutes. Inject the mixed slurry into the mold, and oscillate the mold to make the slurry liquid level flat. Freeze in a -20 to -40°C refrigerator for 2 to 6 hours, and freeze-dry to obtain a preliminary formed high-strength collagen artificial bone repair material.
[0064] In step (2-3), the mass ratio of collagen to calcium phosphate powder is 0.05-1, the mass ratio of collagen to calcium phosphate collagen composite particles is 0.03-0.2, the mass percentage of collagen in the collagen acid solution is 5-10%, the concentration of the acid solution is 0.2-10wt%, and the concentration of the cross-linking agent in the slurry is 10-500ppm.
[0065] The process of step (2-4) is specifically as follows: immersing the initially formed high-strength collagen artificial bone repair material in a crosslinking agent solution, performing a second chemical crosslinking for 6 to 48 hours, placing it in pure water for stirring and washing at 200 to 600 rpm for 6 to 24 hours, and then freeze-drying it to obtain a high-strength collagen artificial bone repair material. The crosslinking agent includes but is not limited to genipin, glutaraldehyde, carbodiimide, etc., with a concentration of 0.05 to 5wt%.
[0066] In the second preparation method, the pre-prepared surface-acidified calcium phosphate collagen composite particles are added to the mixture of collagen and calcium phosphate, which greatly improves the density of the artificial bone repair material and significantly enhances the compressive strength of the material. In addition, the high-strength collagen artificial bone repair material formed twice has a high degree of cross-linking, and its in vivo stability is greatly enhanced.
[0067] Preferably, the calcium phosphate powder used in the above steps is tricalcium phosphate powder containing or not containing magnesium. Specifically, the tricalcium phosphate powder material is prepared by the following steps: dissolving calcium salt and magnesium salt in water to obtain a first solution, wherein the concentration of the calcium salt is 1 to 100 g / L, and the concentration of the magnesium salt is 0.4 to 40 g / L. Furthermore, the molar ratio of calcium ions to magnesium ions is 6 to 10; phosphate is dissolved in water, and an alkali solution (preferably ammonia water or sodium hydroxide) is used to adjust the pH to 9.5 to 10.5 to obtain a second solution, wherein the concentration of phosphate is 1 to 100 g / L; equal volumes of the first solution and the second solution are heated to 60 to 95° C. and then mixed, and a wet chemical reaction is carried out at a temperature of 60 to 95° C. and under stirring conditions at normal pressure, wherein the stirring rate is 100 to 500 rpm, and the molar ratio of calcium ions to phosphate ions is 1.1 to 1.5; the suspension after the wet chemical reaction is centrifuged to obtain a precipitate, which is centrifugally washed with water for 4 to 8 times, and the washed precipitate is added to 5 to 20 times the mass of water, stirred evenly to form a slurry, and the sizing agent is processed into a porous tricalcium phosphate powder using a spray dryer, wherein the inlet air temperature of the spray dryer is 240 to 300° C., the outlet air temperature is 120 to 150° C., and the feed rate is 30 to 200 mL / min.
[0068] The calcium salt is selected from a combination of one or more of anhydrous calcium chloride, calcium chloride dihydrate and calcium nitrate tetrahydrate, the magnesium salt is selected from magnesium chloride hexahydrate and / or magnesium nitrate hexahydrate, and the phosphate is selected from a combination of multiple of disodium hydrogen phosphate, diammonium hydrogen phosphate and sodium hydrogen phosphate. The porous tricalcium phosphate powder has a porous structure, and the specific content of magnesium element therein shows better biological activity and effectively promotes new bone formation. Compared with hydroxyapatite, the porous tricalcium phosphate powder material has better degradation performance, and thus has significant advantages in the application of bone repair materials.
[0069] The artificial bone repair material prepared by the above method solves the following problems:
[0070] (1) Insufficient density and compressive strength
[0071] By compressing and dehydrating during the cross-linking process, the density of the composite material can be increased by 2 to 8 times. An innovative discovery was made that a metastable state exists in the collagen sponge during the chemical cross-linking process. In this state, the free water inside the collagen can be removed by squeezing, and the remaining bound water can be distributed in the sponge to reshape the cross-linking network of the collagen sponge, thereby achieving the purpose of compressing and densifying the sponge network structure. It is also possible to add the pre-prepared surface-acidified calcium phosphate collagen composite powder to the mixed collagen solution. Under the action of the cross-linking agent, the surface of the solid composite particles dissolves and composites with the collagen molecules in the solution to form a high-density collagen / calcium phosphate composite product, which greatly improves the density of the artificial bone repair material and significantly enhances the compressive strength of the material.
[0072] (2) Problem of too fast degradation time
[0073] By significantly increasing the density of the collagen / tricalcium phosphate composite material, the degradation time in vivo is effectively extended. Compared with the traditional sponge compaction molding method, the high-strength collagen artificial bone repair material formed by two moldings has a high degree of cross-linking and greatly enhanced in vivo stability.
[0074] The prepared high-strength collagen artificial bone repair material has a porosity of 20-80% and a compressive strength of 0.5-2Mpa, which is 10-50 times higher than the original material. After implantation into the human body, the degradation time can be effectively prolonged, which can better match the growth rate of new bone.
[0075] The magnesium-containing tricalcium phosphate powder used in the following examples and comparative examples was prepared by the following steps:
[0076] Weighing and dissolving: weigh 900 g of anhydrous calcium chloride and 270 g of magnesium chloride hexahydrate, dissolve in 10 L of water to obtain solution A; weigh 830 g of diammonium hydrogen phosphate, dissolve in 10 L of water, and use ammonia water to adjust the pH value of the solution to 10.0 to obtain solution B.
[0077] Heating and mixing: Heat solution A and solution B to 70°C and mix them, and continue stirring at 100 rpm to form a suspension.
[0078] Wet chemical reaction: The mixed suspension was heated and stirred at 70°C and 100 rpm for 12 hours.
[0079] Centrifugal washing: The suspension after the wet chemical reaction was centrifuged at 2000 rpm for 3 minutes to obtain the precipitate, and water was added and centrifuged for washing 5 times.
[0080] Spray drying: Add the washed precipitate to 10L of water and stir to form a slurry. Set the spray dryer inlet temperature to 250°C and outlet temperature to 120°C, spray dry the slurry at a rate of 50mL / min, and finally obtain tricalcium phosphate powder with a particle size distribution in the range of 1 to 20μm.
[0081] Example 1
[0082] Preparation of calcium phosphate collagen composite particles: Use an analytical balance to weigh 1g of bovine type I collagen and 10g of acetic acid solution with a concentration of 1wt%, add the collagen sponge to the acetic acid solution, and use a PTFE stirring paddle at 500rpm to stir for 30 minutes until completely dissolved. Use an analytical balance to weigh 5.5g of magnesium-containing tricalcium phosphate powder, add all of the magnesium-containing tricalcium phosphate powder to the collagen solution, and continue stirring for 10 minutes until the mixture is evenly mixed. Then, freeze in a -40℃ refrigerator for 3 hours and freeze-dry to obtain a calcium phosphate collagen composite sponge. Use a pelletizer to crush the calcium phosphate collagen composite sponge and obtain powder particles between 20 and 300 meshes.
[0083] Weighing and dissolving: Use an analytical balance to weigh 0.3g of bovine type I collagen and 30g of 1wt% acetic acid solution, add the collagen sponge to the acetic acid solution, and stir with a tetrafluoroethylene stirring paddle at 500rpm for 30 minutes until completely dissolved. Also weigh 6g of calcium phosphate collagen composite particles and add 3g of 1wt% acetic acid solution for acidification, and then add to the collagen acid solution after acidification.
[0084] Mixing configuration: Add 1.5 g of magnesium-containing tricalcium phosphate and stir with a tetrafluoroethylene stirring paddle at 500 rpm for 10 minutes until completely dissolved. Add 3 mL of 1 wt.% glutaraldehyde solution to the mixed solution and stir with a tetrafluoroethylene stirring paddle at 500 rpm for 1 minute.
[0085] Injection molding: Inject the mixed slurry into the mold, shake the mold to make the slurry liquid level flat. Freeze in a -40℃ refrigerator for 6 hours and then freeze-dry to obtain a preliminary high-strength collagen artificial bone repair material.
[0086] Cross-linking and cleaning: the composite material was immersed in a 1 wt.% glutaraldehyde solution for 12 hours, and then placed in pure water for cleaning at 400 rpm for 12 hours.
[0087] Freeze drying: The cleaned sample was placed in a -40℃ refrigerator for 6 hours, and then freeze-dried for 48 hours to obtain a high-strength collagen artificial bone repair material (see the appearance photo for details). Figure 1 ).
[0088] Detection: The microscopic morphology of the prepared high-strength collagen artificial bone repair material can be found in Figure 2 The measured compressive strength is 1560kPa. Figure 3After being immersed in 120 μg / mL type I collagenase at 37°C for 30 days, the high-strength collagen artificial bone repair material of this embodiment that has undergone two cross-linkings did not show obvious degradation, and had high biological stability (see Figure 4 left side).
[0089] Example 2
[0090] Weighing and dissolving: Use an analytical balance to weigh 1 g of bovine type I collagen and 100 g of 1 wt% acetic acid solution, add the collagen sponge into the acetic acid solution, and use a tetrafluoroethylene stirring paddle to stir at 400 rpm for 30 minutes until it is completely dissolved.
[0091] Mixing configuration: Add 6 g of magnesium-containing tricalcium phosphate and stir with a tetrafluoroethylene stirring paddle at 400 rpm for 10 minutes until completely dissolved. Add 1 mL of 1 wt.% glutaraldehyde solution to the mixed solution and stir with a tetrafluoroethylene stirring paddle at 400 rpm for 1 minute.
[0092] Freeze cross-linking: The mixed slurry is injected into a mold, and the mold is shaken to make the slurry liquid level flat. After freezing in a -20°C refrigerator for 7 days, it is taken out and restored to room temperature to obtain a collagen sponge hydrogel.
[0093] Compression dehydration: The collagen hydrogel obtained by freeze cross-linking is placed in a compression mold and compressed to 30% of the initial height. After dehydration, the weight drops to 30% of the initial weight, and freeze-dried to obtain a collagen sponge material.
[0094] Cross-linking and cleaning: The collagen sponge was immersed in a 1 wt.% glutaraldehyde solution for 6 hours, and then placed in pure water for cleaning at 400 rpm for 6 hours.
[0095] Freeze drying: The cleaned samples were placed in a -40°C refrigerator for 3 hours, and then freeze dried for 36 hours to finally obtain a high-strength collagen artificial bone repair material with a measured compressive strength of 420 kPa.
[0096] Example 3
[0097] Preparation of calcium phosphate collagen composite particles: Use an analytical balance to weigh 1g of bovine type I collagen and 10g of acetic acid solution with a concentration of 1wt%, add the collagen sponge to the acetic acid solution, and use a PTFE stirring paddle at 500rpm to stir for 30 minutes until completely dissolved. Use an analytical balance to weigh 5.5g of magnesium-containing tricalcium phosphate powder, add all of the magnesium-containing tricalcium phosphate powder to the collagen solution, and continue stirring for 10 minutes until the mixture is evenly mixed. Then, freeze in a -40℃ refrigerator for 3 hours and freeze-dry to obtain a calcium phosphate collagen composite sponge. Use a pelletizer to crush the calcium phosphate collagen composite sponge and obtain powder particles between 20 and 300 meshes.
[0098] Weighing and dissolving: Use an analytical balance to weigh 0.3g of bovine type I collagen and 30g of 1wt% acetic acid solution, add the collagen sponge to the acetic acid solution, and stir with a tetrafluoroethylene stirring paddle at 500rpm for 30 minutes until completely dissolved. Also weigh 6g of calcium phosphate collagen composite particles and add 3g of 1wt% acetic acid solution for acidification, and then add to the collagen acid solution after acidification.
[0099] Mixing configuration: Add 1.5 g of magnesium-containing tricalcium phosphate and stir with a tetrafluoroethylene stirring paddle at 500 rpm for 10 minutes until completely dissolved. Add 3 mL of 1 wt.% glutaraldehyde solution to the mixed solution and stir with a tetrafluoroethylene stirring paddle at 500 rpm for 1 minute.
[0100] Injection molding: The mixed slurry is injected into the mold, and the mold is shaken to make the slurry liquid level flat. After freezing in a -40℃ refrigerator for 6 hours, freeze drying is performed to obtain the artificial bone repair material. After soaking in 120μg / mL type I collagenase at 37℃ for 30 days, the single cross-linked artificial bone repair material of this example is partially degraded (see Figure 4 on the right).
[0101] Comparative Example
[0102] Weighing and dissolving: Use an analytical balance to weigh 0.5 g of bovine type I collagen sponge, 4.5 g of magnesium-containing tricalcium phosphate powder, and 40 g of 1 wt.% acetic acid solution. Add all the collagen sponge to the solution. Use a tetrafluoroethylene stirring paddle at 400 rpm to stir for 30 minutes.
[0103] Mixing configuration: Add all the magnesium-containing tricalcium phosphate powder to the collagen solution, and stir at 400 rpm using a tetrafluoroethylene stirring paddle for 10 minutes. Add 0.5 mL of 1 wt.% glutaraldehyde solution to the mixed solution, and stir at 400 rpm using a tetrafluoroethylene stirring paddle for 1 minute.
[0104] Injection molding: Inject the mixed slurry into the mold, shake the mold to make the slurry liquid level. Cross-link at -4 degrees for 1 hour, then put the mold into a -40 degrees low-temperature storage cabinet for 4 hours, and demold and take out the initially formed composite material.
[0105] Cross-linking and cleaning: the composite material was immersed in a 1 wt.% glutaraldehyde solution for 6 hours, and then placed in pure water for cleaning at 400 rpm for 6 hours.
[0106] Freeze drying: The cleaned sample is placed in a -40 degree refrigerator and frozen for 6 hours, and then freeze-dried for 36 hours to finally obtain a high-strength collagen artificial bone repair material.
[0107] Test: The compressive strength of the prepared artificial bone repair material is 34 kPa. Figure 3 As shown on the left side, the compressive strength is much lower than that of Example 1.
[0108] As shown in this specification and claims, the terms "comprises" and "include" only indicate the inclusion of the steps and elements that have been clearly identified, and these steps and elements do not constitute an exclusive list, and the method or device may also include other steps or elements. The term "and / or" as used herein includes any combination of one or more of the relevant listed items.
[0109] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0110] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art. If there is any conflict or inconsistency between the definitions used herein and the definitions contained in other public documents, the definitions used herein shall prevail.
[0111] The above embodiment is only for illustrating the technical concept and features of the present invention, and is a preferred embodiment. Its purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and it cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an artificial bone repair material, characterized in that: Using collagen and calcium phosphate as raw materials, forming an artificial bone repair material through the following step S100 or step S200; Step S100 includes: mixing a collagen solution and calcium phosphate, and adding a cross-linking agent to obtain a collagen hydrogel, compressing to remove free water in the hydrogel to reduce the volume of the hydrogel, and freeze-drying to form a collagen hydrogel; Step S200 includes: preparing calcium phosphate collagen composite particles by mixing collagen and calcium phosphate uniformly, weighing the collagen composite particles and calcium phosphate powder and adding them into a collagen solution, adding a cross-linking agent for cross-linking, and freeze-drying to form.
2. The preparation method according to claim 1, characterized in that: Freeze drying molding includes primary freeze drying molding and secondary freeze drying molding. The composite material after primary freeze drying molding is immersed in a crosslinking agent solution for secondary chemical crosslinking. The composite material after secondary chemical crosslinking is cleaned and then subjected to secondary freeze drying molding to obtain the high-strength artificial bone repair material.
3. The preparation method according to claim 2, characterized in that: The secondary chemical cross-linking time is 6 to 48 hours, and the cleaning is carried out by placing it in pure water and stirring it at 200 to 600 rpm for 6 to 24 hours. The cross-linking agent in the cross-linking agent solution includes a combination of one or more selected from genipin, glutaraldehyde and carbodiimide, and the concentration of the cross-linking agent in the cross-linking agent solution is 0.05 to 5wt%.
4. The preparation method according to claim 1, characterized in that: In step S100, after adding a cross-linking agent, the mixture is frozen and cross-linked at -40 to -20°C for 0.5 to 7 days, and then restored to room temperature to obtain a collagen hydrogel; the collagen hydrogel is placed in a compression mold for compression and dehydration, wherein the volume of the collagen hydrogel is compressed to 10 to 70% of the initial volume.
5. The preparation method according to claim 4, characterized in that: Step S100 specifically includes: Step S101, weighing collagen and adding it to an acid solution to obtain a collagen acid solution, adding calcium phosphate powder and mixing evenly, adding a cross-linking agent and stirring evenly to obtain a slurry, injecting the slurry into a molding mold, freezing cross-linking, demolding and returning to room temperature to obtain a collagen hydrogel; Step S102, placing the collagen hydrogel into a compression mold for compression dehydration, and then freeze-drying to obtain a preliminarily formed composite material; Step S103, immersing the initially formed composite material in a crosslinking agent solution to perform a second chemical crosslinking, washing the composite material after the second chemical crosslinking with pure water, and performing a second freeze-drying to obtain the high-strength artificial bone repair material.
6. The preparation method according to claim 5, characterized in that: In step S101, the weight ratio of collagen to calcium phosphate powder is 0.05-1, the mass percentage of collagen in the collagen acid solution is 5-10%, the concentration of the acid solution is 0.2-10wt%, and the concentration of the crosslinking agent in the slurry is 10-500ppm.
7. The preparation method according to claim 1, characterized in that: In step S200, calcium phosphate powder is added to the acid solution of collagen, mixed evenly, freeze-dried and mechanically crushed to obtain calcium phosphate collagen composite particles; the mesh size of the composite particles is 20-300.
8. The preparation method according to claim 7, characterized in that: In step S200, the collagen composite particles and calcium phosphate powder are added to the collagen acid solution, mixed evenly, and then a cross-linking agent is added and mixed evenly to obtain a slurry, which is freeze-dried.
9. The preparation method according to claim 8, characterized in that: Step S200 specifically includes: Step S201, weighing collagen and adding it to an acid solution to obtain a collagen acid solution, adding calcium phosphate powder and mixing evenly, injecting the slurry into a molding mold and freeze-drying to obtain a calcium phosphate collagen composite sponge, and obtaining calcium phosphate collagen composite particles by mechanical crushing; Step S202, weighing calcium phosphate collagen composite particles and adding them into an acid solution to obtain acidified calcium phosphate collagen; Step S203, weighing collagen and adding it to an acid solution to obtain a collagen acid solution, adding calcium phosphate powder and the calcium phosphate collagen acidified in step S202, mixing evenly, adding a cross-linking agent and stirring evenly, injecting the slurry into a molding mold, and freeze-drying to obtain a preliminarily formed composite material; Step S204, immersing the initially formed composite material in a crosslinking agent solution to perform a second chemical crosslinking, washing the composite material after the second chemical crosslinking with pure water, and performing a second freeze-drying to obtain the high-strength artificial bone repair material.
10. The preparation method according to claim 9, characterized in that: In steps S201 and S203, the weight ratio of collagen to calcium phosphate powder is 0.05-1, the mass percentage of collagen in the collagen acid solution is 5-10%, and the concentration of the acid solution is 0.2-10wt%; in step S202, the concentration of the acid solution is 0.2-10wt%, and the mass ratio of calcium phosphate collagen composite particles to the acid solution is 0.5-3; in step S203, the mass ratio of collagen to acidified calcium phosphate collagen is 0.03-0.2, and the concentration of the chemical crosslinking agent in the slurry is 10-500ppm.
11. The preparation method according to any one of claims 1 to 9, characterized in that: The collagen includes a combination of one or more selected from type I collagen, type II collagen and recombinant collagen, and the weight average molecular weight is 50,000 to 300,000 Da; the acid solution includes a hydrochloric acid solution or an acetic acid solution, the calcium phosphate includes a combination of one or more selected from tricalcium phosphate, magnesium-containing tricalcium phosphate, hydroxyapatite and octacalcium phosphate, and the cross-linking agent includes genipin and / or glutaraldehyde.
12. An artificial bone repair material, characterized in that: The artificial bone repair material is prepared according to the preparation method according to any one of claims 1 to 11.
Citation Information
Cited By
Shapeable collagen-based artificial bone repair material as well as preparation method and application thereof
CN121466380A
A malleable collagen-based artificial bone repair material, its preparation method and application
CN121466380B